IRGM1 links mitochondrial quality control to autoimmunity - Rai, Prashant; Janardhan, Kyathanahalli S.; Meacham, Julie; Madenspacher, Jennifer H.; Lin, Wan-Chi; Karmaus, Peer W. F.; Martinez, Jennifer; Li, Quan-Zhen; Yan, Mei; Zeng, Jialiu; Grinstaff, Mark W.; Shirihai, Orian S.; et al. (Nature immunology, 2021)
Mitochondrial abnormalities have been noted in lupus, but the causes and consequences remain obscure. Autophagy-related genes ATG5 , ATG7 and IRGM have been previously implicated in autoimmune disease. We reasoned that failure to clear defective mitochondria via mitophagy might be a foundational driver in autoimmunity by licensing mitochondrial DNA–dependent induction of type I interferon. Here, we show that mice lacking the GTPase IRGM1 (IRGM homolog) exhibited a type I interferonopathy with autoimmune features. Irgm1 deletion impaired the execution of mitophagy with cell-specific consequences. In fibroblasts, mitochondrial DNA soiling of the cytosol induced cyclic GMP-AMP synthase (cGAS)–stimulator of interferon genes (STING)-dependent type I interferon, whereas in macrophages, lysosomal Toll-like receptor 7 was activated. In vivo, Irgm1 –/– tissues exhibited mosaic dependency upon nucleic acid receptors. Whereas salivary and lacrimal gland autoimmune pathology was abolished and lung pathology was attenuated by cGAS and STING deletion, pancreatic pathology remained unchanged. These findings reveal fundamental connections between mitochondrial quality control and tissue-selective autoimmune disease. Fessler and colleagues report that loss of the IFN-γ-induced GTPase IRGM1 results in autoinflammatory disease. Deficient IRGM1 activity led to defective lysosomal maturation and impaired mitophagy, prompting the release of cytosolic mtDNA and thereby activating the cGAS–STING pathway.